Kusta Multibasiler dengan Reaksi Tipe 2 pada Dewasa Muda: Laporan Kasus: Laporan Kasus - Prakoeswa, Flora Ramona Sigit; Islamuddin, Tri Kurnia Ahmad; Dzikri, Dykall Naf'an; Pramuningtyas, Ratih (PT Kalbe Farma Tbk., 2025)
Introduction: Leprosy or Hansen’s disease, is a chronic granulomatous infection caused by Mycobacterium leprae, which affects the skin and peripheral nerves. The disease occurs more frequently in males and remains a significant public health issue in endemic countries such as Indonesia. Case: A 23-year-old male presented with swelling of both hands, feet, and ears, accompanied by numbness and radiating pain. Dermatological examination revealed multiple erythematous papules and nodules that were anesthetic and symmetrically distributed, accompanied by onychodystrophy. Enlargement of the auricularis magnus and posterior tibial nerves was observed, as well as sensory disturbance in the ulnar nerve area. Slit-skin smear examination of the left ear showed acid-fast bacilli (2+ bacilli per field of view). Discussion: The patient was diagnosed with multibacillary-type leprosy with a type 2 reaction (erythema nodosum leprosum). This reaction represents a complex immune response that can lead to permanent nerve damage if not promptly managed. Conclusion: Comprehensive management involving a combination of anti-leprosy drugs, corticosteroids, analgesics, vitamin B complex, and medical rehabilitation is essential to prevent disability progression and improve functional outcomes. Patient education and regular follow-up are crucial for treatment success. The main challenge in this case is to prevent disability progression and maximize remaining function through comprehensive rehabilitation.